Investing in Shares of Commercial Banks in Nepal: An Assessment of Return and Risk Elements - Paudel, Narayan Prasad (NRB Economic Review, 2002)
An attempt has been made in this paper to determine whether the shares of commercial banks in Nepal are correctly priced and to trace their future price movements when striving towards equilibrium. For this, some theoretical models have been discussed to analyze return and risk characteristics of those shares. The correlation coefficients between the returns on individual shares and the return on market portfolio have been analyzed with the objective of decomposing the total risk into systematic and unsystematic components. The analysis of the individual stock's beta coefficient helps determine the minimum rate of return required by the investor to compensate for systematic risk. Statistical results suggest that the analyzed shares here are not in equilibrium with most of the shares being less risky than the market. While all the shares examined appear to be attractive to the potential investors since they produce higher rates of return than that of the average stock, the various shares have different degrees of risk with some shares being unable to generate the minimum rate of return (i.e. the sum of risk free-rate plus a premium for additional risk bearing).